Kegiatan Membantu Pembangunan Jalan Dan Irigasi - Rajiman; Ilyas Sadad; Aditya Mahatidanar Hidayat; Sugito (CV. Multi Kreasi Media, 2022)
The central government in recent years has disbursed village funds throughout the province of Lampung. Allocation of village funds (ADD) is channeled to advance infrastructure development, especially road construction and village irrigation. Tulung Agung Village, Gading Rejo District, Tanggamus Regency is one of the villages that carries out road construction and irrigation. This activity was carried out in June 2021. The method used in this research is coordination. This activity aims to help villages in their efforts to improve infrastructure. The form of this activity is socialization and technical guidance regarding the construction of roads and village irrigation.